Berat Larva Spodoptera litura dan Luas Daun Cabai yang Dimakannya setelah Diaplikasikan Berbagai Isolat Jamur Entomopatogen - Mimma Gustianingtyas; Siti Herlinda; Erise Anggraini; Arsi Arsi; Suwandi Suwandi; Hasbi Hasbi; Marieska Verawaty; Arum Setiawan; Elfita Elfita; Suparman Suparman; Harman Hamidson; Khodijah Khodijah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Gustianingtyas M, Herlinda S, Anggraini E, Arsi A, Suwandi S, Hasbi H, Verawaty M, Setiawan A, Elfita E, Suparman S, Hamidson H, Khodijah K. 2020. Weight of spodoptera litura larvae and chili leaf area eaten after treated with some entomopathogenic fungal isolates. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Spodoptera litura is one of the important insect pests on chili in Indonesia that attacks the vegetative and generative phases. This study aimed to observe the effect of the entomopathogenic fungal isolates explored from the low and highlands on the decrease in feed and weight of S. litura larvae. The experiment was arranged in a Randomized Block Design (RBD) with 52 treatments consisted of 29 isolate of Beauveria bassiana and 23 isolate of Metarhizium spp. applied on 25 second instar of S. litura per replicate. The results showed that the body weight of larvae applied to B. bassiana isolates on the first day of observation was significantly different from the control. The body weight of larvae on the first day of observation of BJgTs isolates (0.30 g) and Bby (0.31 g) was significantly different and lower than the other treatments. The body weight of larvae applied isolate Metarhizium spp. significantly different from the controls. The body weight of larvae on the 9 day applied isolates MPdMs2 (4.74) and MKbTp2 (4.63) was significantly different from other treatments, the leaf area eaten was significantly different from the 7 day to the 12 day of observation. From this research, it can be concluded that B. bassiana isolates coded BJgTs and Bby, isolates Metarhizium spp. MPdMs2 and MKbTp2 codes are isolates that have an effect on reducing feed and larvae weight and cause changes in behavior of S. litura larvae.